PROSPEK PENGEMBANGAN TANAMAN SUKUN DITINJAU DARI KANDUNGAN KIMIA DAN ASPEK LAINNYA - Gusmailina Gusmailina; Sri Komarayati (Jurnal Penelitian Hasil Hutan, 1994)
Breadfruit  (Artocarpus artilis  Forsberg) is  a multipurpose tree species  which  is suitable  to be extensified.  The report  deals with. chemical analysis  of  breadfruit wood. The  results indicated  that  cellulose contenl  53.58 %;  lignin cotuet 28.09%;  pentosan    content 14.00%;  solubitity in cold  water 3.13  % ;  in hot waler  4. 14 %;  alcohol-benzena 3. 40% and in NaOH 1 %  20. 03 % ,  moisture content 10.14 %; ash comesu 3. 60%; silica content  3. 10% and calorific value 4368.82  kcal/gr. Baseak on the components,  breadfruit  wood  can  be utilized  as sources of raw material for pulp  and paper  or rayon.  Besides it is also an alternative for food source and source of income for rural people.